Perceptions, practices and health seeking behaviour constrain JE/AES interventions in high endemic district of North India - Sanjay Chaturvedi; Neha Sharma; Manish Kakkar (BMC, 2017)
Abstract Background Acute Encephalitis Syndrome (AES) and Japanese Encephalitis (JE) stay as poorly understood phenomena in India. Multiple linkages to determinants such as poverty, socio-economic status, gender, environment, and population distribution, make it a greater developmental issue than just a zoonotic disease. Methods A qualitative study was conducted to map knowledge, perceptions and practices of community and health systems level stakeholders. Seventeen interviews with utilizers of AES care, care givers from human and veterinary sectors, Non-governmental Organizations (NGOs), and pig owners and 4 Focused Group Discussions (FGDs) with farmers, community leaders, and students were conducted in an endemic north Indian district-Kushinagar. Results Core themes that emerged were: JE/AES been perceived as a deadly disease, but not a major health problem; filthy conditions, filthy water and mosquitoes seen to be associated with JE/AES; pigs not seen as a source of infection; minimal role of government health workers in the first-contact care of acute Illness; no social or cultural resistance to JE vaccination or mosquito control; no gender-based discrimination in the care of acute Illness; and non-utilization of funds available with local self govt. Serious challenges and systematic failures in delivery of care during acute illness, which can critically inform the health systems, were also identified. Conclusion There is an urgent need for promotive interventions to address lack of awareness about the drivers of JE/AES. Delivery of care during acute illness suffers with formidable challenges and systematic failures. A large portion of mortality can be prevented by early institution of rational management at primary and secondary level, and by avoiding wastage of time and resources for investigations and medications that are not actually required.